(untitled) (Australia,Mason, Ohio, 2004)
This very successful textbook is distinguished by a superior writing style that draws upon common reader experiences to introduce economic concepts, making economic theory more accessible and interesting. "Case Studies" and numerous examples take advantage of readers' intuitive knowledge of economics, building upon real-life situations. A streamlined design places pedagogy and illustrations directly within the flow of the text, making them less distracting and more useful for readers. A fully integrated program of technology enhancements sets this text apart by pairing the book with numerous online multimedia learning tools that have been developed to help the text better serve a wide range of learning styles.
Keywords: Macroeconomics,Kinh tế vĩ mô; Textbooks,Sách giáo khoa